Praktik Sanggar Guru Y.B. Mangunwijaya Sebagai Bentuk Komunitas Guru Belajar Secara Kontinyu - Antonius Wahyu Pradana; Carolus Borromeus Mulyatno (Peneliti.net, 2022)
Sanggar Guru is a marker of the existence of a student community in the school. The learning community reminds teachers that they will be a source of learning, so it is necessary to continue learning. Thus, a learning climate will be formed in schools, not only for students but also for teachers. Sanggar Guru becomes a means of meeting between teachers and learning together in an assisted manner. Sanggar Guru is a term used to describe the habitus and learning community inherited by Y.B Mangunwijaya. Sanggar Guru is supported by the Mangunan Experimental School and Dinamika Edukasi Dasar Foundation . The study was conducted using a qualitative approach and the method of focus group discussion (FGD), this study aims to review the extent to which Sanggar Guru is a learning community that is able to foster a learning climate in schools. The thoughts of Y.B Manunwijaya and several figures became the analytical framework for the data found. There are several important points found in this study, namely Sanggar Guru as a learning community has a theme, continuous time, has output and there is documentation. In addition, the Sanggar Guru is carried out according to the school's vision and mission. The basic thing that is important is the awareness and willingness of teachers to continue learning. Through this teacher workshop, it was found that the teachers felt they were growing and developing each other among their colleagues.